2010
DOI: 10.3109/15368371003776725
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectromagnetic Field Effects on Cancer Cells and Mice Tumors

Abstract: We present possibilities and trends of ELF bioelectromagnetic effects in the mT amplitude range on cancer cells and on mice bearing tumors. In contrast to invasive electrochemotherapy and electrogenetherapy, using mostly needle electrodes and single high-amplitude electropulses for treatment, extremely low-frequency (ELF) pulsating electromagnetic fields (PEMF) and sinusoidal electromagnetic fields (SEMF) induce tumor cell apoptosis, inhibit angiogenesis, impede proliferation of neoplastic cells, and cause nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…It should be noted that electromagnetic (EM) fields may affect the regulation of cellular growth and differentiation, including the growth of tumors [9,10]. Both static magnetic and electric fields have altered the mitotic index and cell cycle progression of a number of cell types in various species [10].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that electromagnetic (EM) fields may affect the regulation of cellular growth and differentiation, including the growth of tumors [9,10]. Both static magnetic and electric fields have altered the mitotic index and cell cycle progression of a number of cell types in various species [10].…”
Section: Introductionmentioning
confidence: 99%
“…While several studies suggested that EMF exposure induces immune cell activation and DNA damage (10,11), the findings of other studies indicated that the effects of EMF inhibit preneoplastic lesions, resulting in the reduction of cell proliferation (3). A number of studies focused on the potential effects of EMF at cancer treatment (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Berg also illustrated effects of bioelectromagnetic in the mT amplitude range on cancer cells on mice. He fide out that synergic combination of extremely low-frequency (ELF) pulsating electromagnetic fields (PEMF) and sinusoidal electromagnetic fields (SEMF) induce tumor cell apoptosis, inhibit angiogenesis and proliferation of cells and cause necrosis [19]. Another research reveals that the expression levels of angiopoietin-2 and fibroblast growth factor-2 were significantly higher in the PEMF group than in the control group while lack of rise in the expression level of vascular endothelial growth factor suggests that PEMF does not have invasive effects including the induction of hypoxic conditions and inflammation on the bone marrow [20].…”
Section: Discussionmentioning
confidence: 99%